2017
DOI: 10.1039/c6cp06448e
|View full text |Cite
|
Sign up to set email alerts
|

Towards improved halogenated BODIPY photosensitizers: clues on structural designs and heavy atom substitution patterns

Abstract: The singlet oxygen (O) production quantum yield (Φ) of 14 halogenated BODIPY dyes has been determined (0.01 < Φ < 0.99). O production and photostability have been evaluated considering the BODIPY structure, the substitution pattern, and the number and type of heavy atoms and quenching rate constants of O by the sensitizer. In view of the experimental results and principal component analysis (PCA), guidelines for an improved design of efficient and photostable halo-BODIPY sensitizers are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The studied haloBODIPYs were based on 8‐tolylBODIPY (Series A; compounds 2‐8 in Fig. 5 and Table 1) (74,75), trialkylBODIPY (Series B; compounds 9‐13 in Fig. 5 and Table 1) (75) and 8‐heteroatom‐substituted BODIPY (Series C; compounds 14‐17 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied haloBODIPYs were based on 8‐tolylBODIPY (Series A; compounds 2‐8 in Fig. 5 and Table 1) (74,75), trialkylBODIPY (Series B; compounds 9‐13 in Fig. 5 and Table 1) (75) and 8‐heteroatom‐substituted BODIPY (Series C; compounds 14‐17 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 and Table 1) (74,75), trialkylBODIPY (Series B; compounds 9‐13 in Fig. 5 and Table 1) (75) and 8‐heteroatom‐substituted BODIPY (Series C; compounds 14‐17 in Fig. 5 and Table 1) (76).…”
Section: Resultsmentioning
confidence: 99%
“…The literature data for similar compounds in non-viscous solvents indicated that significant singlet oxygen production quantum yields (and hence the triplet state yields) are expected for both the alpha-Br and the beta-Br substitution of the BODIPY core. 37 At the same time, the fluorescence quantum yields in non-viscous solvents were not affected, compared to a non-substituted BODIPY. 38 To the best of our knowledge, the viscosity sensitivity of BODIPY dyes modified with Br substituents at the core was not previously investigated.…”
Section: View Article Onlinementioning
confidence: 88%
“…One approach to obtain new molecules is focused on the synthesis of improved PS to overcome their limitations but this usually requires multistep chemistry increasing the costs and production time, hampering the implementation for clinical uses. In this context, BODIPY dyes have recently raised attention as potential photosensitizers [15][16][17][18]. They are characterized by intense absorption and emission bands in the green region and resistance to photobleaching [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being highly fluorescent chromophores (antagonistic property to ROS generation) and poorly soluble in water, their synthesis allows an easy, versatile, and selective modification of their molecular structure to increase the population of the triplet state and consequently their singlet oxygen generation and also shifts their spectroscopic bands into the clinic window. These modifications include the addition of iodine heavy atoms, π-conjugated systems in the BODIPY skeleton, or the design of orthogonal BODIPY dimers [15,17,18,[21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%